Speech Intelligibility of School-aged Children with Cochlear Implants - Tsukahara, Kiyoaki; Saito, Yusuke; Nonami, Naoko; Kawano, Atsushi; Ayusawa, Emi; Tomizawa, Ayako; Shirai, Kyoko (Nippon Jibiinkoka Gakkai Kaiho, 2018)
Objectives: Verbal communication depends on good hearing and clear speech. Previous studies have shown that cochlear implantation at an early age, long implant experience, and high chronological age contribute to speech intelligibility. However, there are as yet few studies on the long-term outcomes in respect of the speech intelligibility in children with cochlear implants. The aim of our study was to identify the factors significantly associated with speech intelligibility in school-age children with cochlear implants.　Methods: The study subjects were 84 school-age, prelingually deaf children who had received cochlear implants between the ages of 2 and 11 years. Speech intelligibility was measured using Speech Intelligibility Rating (SIR), which is composed of five hierarchical categories based on the hearing impression.　We investigated the associations of the following nine factors (age at implantation, implant experience, chronological age, hearing thresholds with the cochlear implant(s), speech perception, verbal and performance IQ as evaluated with the WISC, Japanese reading score, and school type) with the speech intelligibility.　Results: The mean chronological age at evaluation was 13 years. The children had received their cochlear implants at the mean age of 4.3 years, and had 8.6 years of experience, on average, of carrying cochlear implants (implant experience). The mean SIR score was 4.2 (5 being the best), and almost 60% of the children had an SIR score of 5. The mean speech perception score was 82.6%.　Factors that were found to be significantly associated with speech intelligibility were speech perception, school type, verbal IQ, age at implantation, and hearing thresholds with the cochlear implant(s); on the other hand, no association was found with the chronological age, implant experience, performance IQ or the Japanese reading score. In particular, speech perception, school type, and age at implantation were identified as significant predictors of speech intelligibility.　Conclusion: In school-age children with a cochlear implant experience of 8.6 years, good speech perception, mainstream classroom, and early age at implantation were found to be significant predictors of good speech intelligibility.